Impact and flexural properties of ABS biocomposites reinforced with coir fiber - de Souza, Milena Chanes [UNESP]; Moroz, Ivan [UNESP]; Reis, Victor [UNESP]; Cesarino, Ivana [UNESP]; Leão, Alcides Lopes [UNESP] (Elsevier, 2022)
Biocomposites reinforced with natural fibers can generate benefits and be strategic within the circular economy concept, since they can present enhanced mechanical properties, lower production cost, lower density, higher biodegradability and cause less damage to the environment. Coir fiber is easy to access, cheap, has low density and good mechanical properties, presenting perfect properties to be used as reinforcement in composites. In this study, the development of coir fiber-reinforced biocomposites is proposed, to be used mainly as table covers, travel bags, car and aircraft interior panels, among other applications. High stiffness and fair ductility, in addition to having low density, are desirable properties. For this purpose, biocomposites were developed with different coir fiber concentrations (0%, 20%, and 50%) and mechanical properties were evaluated via impact strength and flexural tests. Results of mechanical testing indicated the influence of fiber addition on performance, causing a reduction of impact strength and flexural strength while improving flexural moduli and yielding stiffer materials. The poor interface adhesion between matrix and fiber could be observed by scanning electron microscopy, and was responsible for strength reduction which may be countered by means of additives utilization. Therefore, new studies must be developed to add coupling agents and thus improve fiber adhesion with the matrix. Overall, ABS/coir fibers obtained in this report show interesting potential for practical use representing an option for lower cost, green, sustainable, and renewable biocomposites aligned with the circular economy concept.
Keywords: Acrylonitrile Butadiene Styrene (ABS); Biocomposites; Coir fibers; Flexural strength; Impact strength